PENGARUH INDIKATOR KEBIJAKAN MONETER TERHADAP INFLASI DI INDONESIA - Fatimah Zuhra (Politeknik Negeri Lhokseumawe, 2018)
Abstract : The purpose of this study is to explain whether the interest rate influences inflation in Indonesia and whether the money supply affects inflation in Indonesia. The subject of this research is Bank Indonesia. While object in this research is data of interest rate and money supply in Indonesia from year 1986 - 2016. The type of data used in this research is secondary data. Data analysis method used is quantitative research. Based on partial test results (t test) shows that 1) Interest rates have a positive effect on inflation in Indonesia. 2) The money supply has a positive effect on inflation in Indonesia and Based on the simultaneous test results (F test) it can be concluded that Interest rates and money supply have positive effect on inflation in Indonesia.Keywords: Monetary Policy Indicators, Inflation